Editors’ Foreword - Starkey, Dr Janet (Proceedings of the Seminar for Arabian Studies, 2016)
The Seminar for Arabian Studies is the only international academic forum that meets annually for the presentation of research in the humanities on the Arabian Peninsula. It focuses on the fields of archaeology, architecture, art, epigraphy, ethnography, history, language, linguistics, literature, and numismatics from the earliest times to the present day. In addition, on the evening of Saturday, 25 July 2015, Professor Peter Magee, Director of Middle Eastern Studies, Bryn Mawr College, Philadelphia, USA, a leading expert on the archaeology of Arabia and the formation of Arabian society, presented the MBI Lecture entitled ‘Turning the world upside down: the emergence of camel caravans and overland trade in the Ancient Near East’. He provided an informative, interesting, and lucid lecture regarding the domestication of the dromedary and how its use reconfigured politics and economy in the Ancient Near East.